Redescription of East Palaearctic ground spider Drassyllus biglobus Paik, 1986 (Araneae: Gnaphosidae) - Omelko, Mikhail M.; Marusik, Yuri M.; Kim, Byung-Woo (Zootaxa, 2013)
Drassyllus Chamberlin, 1922 is a fairly large (91 species) Holarctic genus of gnaphosid spiders (Platnick 2013). Although it is a relatively well studied genus thanks to the revisional works of Platnick & Shadab (1982), Grimm (1985), Paik (1992), Kamura (2009) and some other works, 25 species or over 25% remain known from one sex only (four by males and 21 by females).